Integrative transcriptome and metabolome analysis reveals the discrepancy in the accumulation of active ingredients between Lycium barbarum cultivars - Liu, Xuexia; Gao, Han; Radani, Yasmina; Yue, Sijun; Zhang, Ziping; Tang, Jianning; Zhu, Jinzhong; Zheng, Rui (Planta, 2024)
Main conclusion The combined analysis of transcriptome and metabolome provided molecular insight into the dynamics of multiple active ingredients biosynthesis and accumulation across different cultivars of Lycium barbarum . Lycium barbarum L. has a high concentration of active ingredients and is well known in traditional Chinese herbal medicine for its therapeutic properties. However, there are many Lycium barbarum cultivars, and the content of active components varies, resulting in inconsistent quality between Lycium barbarum cultivars. At present, few research has been conducted to reveal the difference in active ingredient content among different cultivars of Lycium barbarum at the molecular level. Therefore, the transcriptome of 'Ningqi No.1' and 'Qixin No.1' during the three development stages (G, T, and M) was constructed in this study. A total of 797,570,278 clean reads were obtained. Between the two types of wolfberries, a total of 469, 2394, and 1531 differentially expressed genes (DEGs) were obtained in the ‘G1 vs. G10,’ ‘T1 vs. T10,’ and ‘M1 vs. M10,’ respectively, and were annotated with Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) orthology identifiers. Using these transcriptome data, most DEGs related to the metabolism of the active ingredients in 'Ningqi No.1' and 'Qixin No.1' were identified. Moreover, a widely targeted metabolome analysis of the metabolites of 'Ningqi 1' and 'Qixin 1' fruits at the maturity stage revealed 1,135 differentially expressed metabolites (DEMs) in ‘M1 vs. M10,’ and many DEMs were associated with active ingredients such as flavonoids, alkaloids, terpenoids, and so on. We further quantified the flavonoid, lignin, and carotenoid contents of the two Lycium barbarum cultivars during the three developmental stages. The present outcome provided molecular insight into the dynamics of multiple active ingredients biosynthesis and accumulation across different cultivars of Lycium barbarum , which would provide the basic data for the formation of Lycium barbarum fruit quality and the breeding of outstanding strains.